2013
DOI: 10.1038/mt.2012.202
|View full text |Cite
|
Sign up to set email alerts
|

Type I IFN Counteracts the Induction of Antigen-Specific Immune Responses by Lipid-Based Delivery of mRNA Vaccines

Abstract: The use of DNA and viral vector-based vaccines for the induction of cellular immune responses is increasingly gaining interest. However, concerns have been raised regarding the safety of these immunization strategies. Due to the lack of their genome integration, mRNA-based vaccines have emerged as a promising alternative. In this study, we evaluated the potency of antigen-encoding mRNA complexed with the cationic lipid 1,2-dioleoyl-3trimethylammonium-propane/1,2-dioleoyl-sn-glycero-3-phosphoethanolamine (DOTAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
176
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(189 citation statements)
references
References 32 publications
(35 reference statements)
7
176
0
2
Order By: Relevance
“…Furthermore, cationic lipids can be immunogenic, which can limit transgene expression and raise safety concerns (88). IFN production in response to lipid-complexed mRNA can limit efficacy of mRNAbased vaccines (34). Various nanoparticle formats have demonstrated varying levels of efficacy through intradermal (89), intrasplenic (90), subcutaneous (34), intravenous (89,91), and even intranasal (92) routes of administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, cationic lipids can be immunogenic, which can limit transgene expression and raise safety concerns (88). IFN production in response to lipid-complexed mRNA can limit efficacy of mRNAbased vaccines (34). Various nanoparticle formats have demonstrated varying levels of efficacy through intradermal (89), intrasplenic (90), subcutaneous (34), intravenous (89,91), and even intranasal (92) routes of administration.…”
Section: Discussionmentioning
confidence: 99%
“…However, delivery is required for replicon mRNA function, and, to date, there has been no report of protective immunity capable of allowing for survival against a lethal challenge of any pathogen using nonviral, fully synthetic approaches (32). Naked replicon mRNA can activate the innate immune system upon administration, which can limit translational efficiency, diminish potency, and induce toxicity (33)(34)(35)(36). RNA, particularly single-stranded RNA, is rapidly degraded by nucleases when injected in vivo (37).…”
mentioning
confidence: 99%
“…The observed increase in Ag expression in mice with abrogated type I IFN signaling may be the result of increased translational efficiency of SAM-encoded Ag. Indeed, it has been reported that type I IFN impairs exogenous mRNA translation (39,40). In addition, as reported by Cruz et al (41), specific single mutations in nsP1 sequence of alphaviruses increase type I IFN levels in vitro as well as in vivo and determine the virus virulence attenuation.…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, in the process of amplification of their genomes, RNA replicons engage pattern recognition receptors in the host cell, adjuvanting the responses to the encoded immunogen (45)(46)(47). Although both mRNA-and replicon RNA-based vaccines were shown to elicit antigen-specific antibody and cellular immune responses against several pathogens (44,(48)(49)(50)(51), the self-amplifying nature of replicon-based vaccines is likely to result in higher levels of antigen expression and in a more effective engagement of innate immune responses than mRNA-based vaccine candidates.…”
mentioning
confidence: 99%